2021 IEEE/CVF Conference on Computer Vision and Pattern Recognition Workshops (CVPRW) 2021
DOI: 10.1109/cvprw53098.2021.00013
|View full text |Cite
|
Sign up to set email alerts
|

From Evaluation to Verification: Towards Task-oriented Relevance Metrics for Pedestrian Detection in Safety-critical Domains

Abstract: Whenever a visual perception system is employed in safety-critical applications such as automated driving, a thorough, task-oriented experimental evaluation is necessary to guarantee safe system behavior. While most standard evaluation methods in computer vision provide a good comparability on benchmarks, they tend to fall short on assessing the system performance that is actually relevant for the given task. In our work, we consider pedestrian detection as a highly relevant perception task, and we argue that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…we cannot generate pedestrian-specific metadata. As also discussed in Lyssenko et al [9] this lacking separability and identifiability of individual pedestrians can be challenging for some more advanced analysis (depthbased in their case) and requires a workaround.…”
Section: Metadata Generation In Carlamentioning
confidence: 99%
See 1 more Smart Citation
“…we cannot generate pedestrian-specific metadata. As also discussed in Lyssenko et al [9] this lacking separability and identifiability of individual pedestrians can be challenging for some more advanced analysis (depthbased in their case) and requires a workaround.…”
Section: Metadata Generation In Carlamentioning
confidence: 99%
“…There is also no issue of domain gap as training, and test data are from the same domain. Parallel to our work, Lyssenko et al [9] present a CARLA-based extension to perform validation of DNNs by considering the pedestrian distance from the ego vehicle as a safety relevance metric. However, they mention that their bounding box retrieval method for getting instances has some issues.…”
Section: Related Workmentioning
confidence: 99%
“…The determination in the use of Device-Free sensors, allows the independence of the system in the collection of data for the identification of the passer-by. The need to establish and depend on equipping the pedestrian with a device segments the type of public to be accounted for [9] , [10] .…”
Section: Hardware In Contextmentioning
confidence: 99%
“…The misalignment between typical perception metrics and application makes it challenging to rely on existing metrics to verify and validate perception algorithms deployed in the real-world. In fact, using a case study on a pedestrian detection algorithm on an AV, [11] showed there was a linear degradation in IoU performance the further away a pedestrian was, therefore indicating that IoU alone is not sufficient in validating safety. As such, they propose two different evaluation metrics that require user-specified inputs.…”
Section: Related Workmentioning
confidence: 99%